Strategi Pemerintah Kota Batu Dalam Rangka Menarik Investor Guna Meningkatkan Pendapatan Asli Daerah - Amalia, Ria (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Abstract: Batu city has a proud economic level, it is based on the increase in the amount of local revenue. Â Increase could not be separated from the strategy that has been formulated in the Batu city government to attract investors. The aim of this paper is to describe the implementation of the strategy has been formulated. Using qualitative methods, the result shows that the Batu city government officials have implemented a good strategy. But there are still many problems encountered in its implementation, to optimize service to investors about the clarity of the policy, transportation and communications. Government should evaluate the implementation of the strategy that has been done, in order to create a government that is good governance. Keywords: Government strategies, Attract investors